The Relationship between Demographic Factors and Financial Knowledge on the Financial Behavior of UPTD Puskesmas Takkalalla Employees in Wajo Regency - Improatin, Improatin; Aisyah, Siti; Khalid, Idham (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the relationship between demographic factors and financial knowledge on the financial behavior of UPTD Puskesmas Takkallala employees of Wajo Regency. The research method used is quantitative with a survey approach using a questionnaire. The research sample consisted of 58 employees selected using the saturated sample technique. The results showed that demographic factors, which include age, gender, and income, have a significant influence on employee financial behavior. In addition, financial knowledge also has a positive effect on individual financial management, including financial planning, budgeting, and investment decision making. The conclusion of this study is that the better the financial understanding of employees, the better their financial behavior. Therefore, improving financial literacy through training and financial education for employees is highly recommended to improve their financial well-being.